2013
DOI: 10.1007/s11251-013-9274-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting critical, elaborative discussions through a collaboration script and argument diagrams

Abstract: During the past two decades a variety of approaches to support argumentation learning in computer-based learning environments have been investigated. We present an approach that combines argumentation diagramming and collaboration scripts, two methods successfully used in the past individually. The rationale for combining the methods is to capitalize on their complementary strengths: Argument diagramming has been shown to help students construct, reconstruct, and reflect on arguments. However, while diagrams c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 54 publications
(91 reference statements)
1
31
0
1
Order By: Relevance
“…The underlying rationale for representational guidance tools is to provide learners with graphical representation of the structure of argumentation to support argumentation processes in the form of schematic representation (Schwarz and De Groot 2007), tables (Suthers and Hundhausen 2003), or visualizations (Noroozi et al 2011;Scheuer et al 2013). The underlying rationale for digital dialogue games is based on the dialogic dimension of argumentation that guides students towards desirable argumentative moves and sequences (see Ravenscroft 2007Ravenscroft , 2011 for an overview) such as CoLLeGE (e.g., Ravenscroft and Pilkington 2000), AcademicTalk (e.g., McAlister et al 2004), and InterLoc (e.g., Ravenscroft and McAlister 2006).…”
Section: Computer Support Systems For Collaborative Argumentation-basmentioning
confidence: 99%
“…The underlying rationale for representational guidance tools is to provide learners with graphical representation of the structure of argumentation to support argumentation processes in the form of schematic representation (Schwarz and De Groot 2007), tables (Suthers and Hundhausen 2003), or visualizations (Noroozi et al 2011;Scheuer et al 2013). The underlying rationale for digital dialogue games is based on the dialogic dimension of argumentation that guides students towards desirable argumentative moves and sequences (see Ravenscroft 2007Ravenscroft , 2011 for an overview) such as CoLLeGE (e.g., Ravenscroft and Pilkington 2000), AcademicTalk (e.g., McAlister et al 2004), and InterLoc (e.g., Ravenscroft and McAlister 2006).…”
Section: Computer Support Systems For Collaborative Argumentation-basmentioning
confidence: 99%
“…Research has shown that collaboration scripts facilitate student collaboration as well as collaboration outcomes. Scheuer, McLaren, Weinberger, and Niebuhr (2014) employed collaboration scripts in conjunction with a visual display of arguments with diagrams on climate ethnics. Results showed that students engaged in more elaborative arguments and demonstrated a more positive attitude in their argumentation learning.…”
Section: Use Of Collaboration Scripts For Collaborative Learningmentioning
confidence: 99%
“…Individual preparation allows students to develop their own reasoning before being influenced by others and is crucial for successful collaboration (Rummel & Spada, 2005;Scheuer et al, 2014). The Questioning step starts by each student asking questions reciprocally based on the headings and subheadings of the article, whereupon students determine the question list through mutual discussion.…”
Section: Use Of Collaboration Scripts For Collaborative Learningmentioning
confidence: 99%
“…It shows that there is importance action need to be taken in order to analyze AKC in education especially to foster students' thinking skills to the higher level. Also, most of the AKC studies focusing on the higher education learning (see Table II) since the researchers focusing on how to improve the students' teachers' course which will reflect on how teachers will be able to teach students using HOTS in future [23,25,28,29,33,35,36,37]. Table III shows that the most frequently used or well-known AKC analysis frameworks in education is Toulmin's Model (4 papers) and Simplified Toulmin (2 papers) which is also originated from Toulmin's model.…”
Section: Rq1: In What Educational Contexts and Levels Has Akc Been Momentioning
confidence: 99%